Antioxidant activity assay of Roselle (Hibiscus sabdariffa) seeds Ethanol extract with DPPH radical scavenging using UV-Vis Spectrophotometer - Syahara, Muhammad Alwi; Helilusiatiningsih, Nunuk; Irawati, Titik (Journal of Natural Sciences and Mathematics Research, 2024)
Hibiscus sabdariffa (Roselle) is known to have a strong antioxidant compound. Thus, the calyx becomes the most important area to research. Another part of this plant that was starting to be known for its benefits is rosella seeds. Roselle seeds are a source of fat-soluble antioxidants. The aim of this study was to investigate the antioxidant activity of Roselle Seed Ethanol Extract (RSEE) with the DPPH (1,1-Diphenyl-2 Picrylhidrazyl) radical scavenging method. This research begins by doing the extraction of Roselle seeds using ethanol (96%) as a solvent and then assessing the antioxidant activity (Radical Scavenging Activity/RSA) of the extract, which is compared with the ascorbic acid standard at several concentrations (5-200 ppm). Antioxidant activity was assessed with DPPH Radical Scavenging using UV-Vis spectrophotometer and IC50 value parameters. The results of this study were the absorbance of DPPH from spectrophotometer at 517 nm was 0,824 (purple color). The absorbance of RSEE and ascorbic acid at 5 ppm to 200 ppm, respectively 0.523-0.124 and 0.594-0.112. The antioxidant activity (RSA) of the RSEE and ascorbic acid, respectively was  57.93% and 59.24%. The IC50 value of RSEE was 30.158 μg/ml and as comparison is ascorbic acid, the IC50 value was 26.948 μg/ml. Thus, the antioxidant activity of roselle seeds ethanol extract (RSEE) belongs to a very strong category (<50 μg /ml). This is due to the presence of several phenolic compounds and unsaturated fatty acid derivatives.